Awareness and Skills of Modern Telemedicine Practice among Doctors in Kerala- A Cross-sectional Study - Anil Bindu Sukumaran; Manju Leela; Kannan Suresh; Himiki Selvin; Regi Jose; Shilpa Prakash; Divija Vijith; PV Benny (Journal of Clinical and Diagnostic Research, 2022)
Introduction: In this modern era of technology, Information and Communication Technology (ICT) has made a very big revolution. Telemedicine is an emerging concept in healthcare services in Kerala, its implementation has not been satisfactory and successful. It is cost effective and provides easy access to healthcare services for people anywhere and especially during pandemic situations like this. A study is required in the domain of awareness and skill of doctors to facilitate its adoption and implementation. There was an urgent need to devise means for patients to consult doctors during Coronavirus Disease 2019 (COVID-19) pandemic. Aim: To assess the level of awareness and skill among doctors practicing modern medicine during COVID-19 pandemic. Materials and Methods: A cross-sectional study was conducted among 535 modern medicine doctors of Kerala from June 2020 to May 2021, using a structured self-administered questionnaire designed for the study. The total scores of awareness and skill calculated and categorised as poor, moderate, and good. Data was analysed by Statistical Package for the Social Sciences (SPSS) version 20.0 software by IBM. The Chi-square test/ Fisher’s-Exact test was used as test of significance. Results: Mean age of the study participants was 40.44±10.66 years, with majority 326 (60.94%) being females. Among the 535 doctors participated, 68.22% had moderate skill, 27.85% had good skill and only 3.92% had poor skill. Years of experience of doctors ranged from 1 to 48 years, with mean of 13.47±10.46 years. In majority, 431 (80.56%) of the participants, had moderate awareness and 15.89% had good awareness, about the telemedicine practice. Poor awareness was present in 19 (3.55%) doctors. About 46.54% believed that specific software training is required for practicing telemedicine. Conclusion: Even though, awareness and skill of doctors practicing modern medicine are favourable, more webinars or workshops are needed to improve their knowledge. Telemedicine is an emerging technology in the health sector in India, so it requires study to know health professional’s awareness and skills towards telemedicine.